Identification of the gamma irradiation dose applied to ground beef that reduces Shiga toxin producing Escherichia coli but has no impact on consumer acceptance. (April 2021) - Cap, M.; Lires, C.; Cingolani, C.; Mozgovoj, M.; Soteras, T.; Gentiluomo, J.; Principe, F.; Sucari, A.; Horak, C.; Signorini, M.; Vaudagna, S.R.; Leotta, G.
Abstract: The aims of the present study were: a) to estimate the minimal dose of gamma irradiation required to reduce 5 log CFU/g of native O157 and non-O157 Shiga toxin-producing Escherichia coli population in ground beef samples inoculated with high inoculum; b) to assess its effectiveness in samples with low inoculum and 3) to evaluate consumer acceptance. Based on the results, 1 kGy was estimated as the minimal dose of gamma irradiation required to reduce 5 log CFU/g of STEC in ground beef. However, when samples with low inoculum level were subjected to 1 kGy, 3.9% of the samples were positive for stx and eae genes after an enrichment step. Consumer acceptance analysis was carried out with samples subjected to 2.5 kGy and no significant differences were found between irradiated and control samples. Therefore, 2.5 kGy was identified as the gama irradiation dose that reduces STEC but has no impact on consumer acceptance of ground beef. Highlights: The D10 values of STEC O157 and four non-O157 strains were between 0.15 and 0.20 kGy. The minimal dose required to reduce 5 log CFU/g of STEC in ground beef was 1 kGy. After 1 kGy, 3.9% of samples with low inoculum were positive for stx and eae genes. After 2.5 kGy, ground beef consumer's acceptance was not affected.